Immune Checkpoint Inhibitors' challenges, mechanisms and management - Yin, Sijie (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Numerous studies have demonstrated that the ability of protecting malignant cells from immune destruction—particularly from T and B lymphocytes, macrophages, and natural killer cells—is linked to the aetiology of cancer. Malignant cells hold the capacity to activate specific immunological checkpoint pathways that have immunodepressant qualities, which is why immunosuppression is connected to the growth and spread of cancer. Immunotherapy has grown to be a crucial method of therapy for cancer. Immune checkpoint blocking increases anti-tumor immunity by preventing intrinsic down-regulated factors of immunity, like CTLA-4 and PD-1, or PD-L1. Unquestionably, ICIs have advanced the area of cancer immunotherapy. In spite of ICIs' success, various challenges to these drugs, such as resistance and immune side effects, have made treatment difficult. Therefore, more in-depth understanding of the mechanism of ICI treatment and its toxicity is needed. Ultimately, on the basis of these insights, biologists will eventually be able to refine ICIs to achieve longer lasting efficacy and improved security. Here, we review the mechanisms and clinical applications of ICIs, examine the various challenges facing ICIs, including the mechanisms of resistance to treatment and the manifestation of irAEs and explore more sound management measures on this basis.